2016
DOI: 10.25134/erjee.v5i1.393
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Approach and Character Education- Based Developing English Textbook

Abstract: This research was conducted with the purpose to develop the materials of textbook based on intercultural approach and character education as a guideline in learning English for senior high school class X in Purworejo regency, and to determine the validity of the development of textbooks. The method used in this research is R and D. Based on the findings, it can be concluded that English book published by the government in 2014 requires improvement in terms of 1) the current topic which are very important becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Further, Rokhayati (2016) developed an English textbook on intercultural approach and character education as guidelines for learning English. From the results of the questionnaire and observation Rokhayati (2016) revealed that English textbooks explicitly mentioned the students' diversity and the target language diversity that knowledge, experience, and discourse reflected in the text (Rokhayati, 2016)…”
Section: Introductionmentioning
confidence: 99%
“…Further, Rokhayati (2016) developed an English textbook on intercultural approach and character education as guidelines for learning English. From the results of the questionnaire and observation Rokhayati (2016) revealed that English textbooks explicitly mentioned the students' diversity and the target language diversity that knowledge, experience, and discourse reflected in the text (Rokhayati, 2016)…”
Section: Introductionmentioning
confidence: 99%
“…Teaching English for specific purposes remains potentials and challenges in the recent years . Many higher educational institutions such as universities and high schools have offered English for specific purposes program as a compulsory subject which becomes one of the primary areas in English as foreign language (EFL) teaching (Septiyana, 2019;Rokhayati, 2016). According to Basturkmen (2014), ESP is an approach to language teaching where all contents and methods are suitable with the students' reasons for learning.…”
Section: Introductionmentioning
confidence: 99%